Implementasi Algoritma Apriori Untuk Prediksi Transaksi Penjualan Produk Pada Aplikasi Point Of Sales - Fathurrozi, Ahmad; Masya, Fajar; Sugiyatno (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
In the face of market competition, in order to increase sales of products sold, related parties must think about strategies for product marketing to increase sales productivity. One of them is by predicting and analyzing sales transaction data on the Point of sales system used. The unavailability of calculation analysis of the formation of a pattern of product associations that are most often purchased by consumers in product sales transaction data. By applying data mining techniques to the association rule method using the a priori algorithm, it can be used as a method to predict and analyze data from sales transactions, this method aims to display information about the data results in the form of a product association pattern that is most often purchased by consumers. With the resulting product association pattern, it will be used to support decision making in making business solutions.